The Development of Learning Activities using Constructivism to Promote Creative A Good Citizenship to The Way of Democracy in Social Studies Subject of Mathayomsuksa 3 Students: The Development of Learning Activities using Constructivism to Promote Creative A Good Citizenship to The Way of Democracy in Social Studies Subject of Mathayomsuksa 3 Students - Siriwat, Pirada (RATANABUTH JOURNAL, 2023)
The​ purpose​ of​ this​ research​ is​ to 1) Create and check the quality of learning activities using constructivism to promote creativity, a​ good​ citizenship to​ the​ way​ of​ democracy in social​ studies subject​ 6 of​ mathayomsuksa 3 students. 2) Study​ the results of​ learning activities using constructivism to promote creativity, a​ good​ citizenship to​ the​ way​ of​ democracy in social​ studies subject​ 6 of​ mathayomsuksa 3 students​ with​ 70​ percent. The research method was divided into 2 steps, steps: 1 create and check the quality of learning activities using constructivism to promote creativity, steps: 2 Study​ the results of​ learning​ activities​ using​ constructivism to compare creativity of​ mathayomsuksa 3 students after learning activities using constructivism​ with​ 70​ percent. The​ sample​ consisted​ of​ 24​ mathayomsuksa 3 students ​from​ 4​ classrooms,​ Implement activities for​ 7​ weeks, the​ data​ were​ analyzed​ using​ t-test (one​ sample), mean ( ) ​ and​ standard​ deviation (S.D.) The​ research​ results​ showed​ that: learning activities using constructivism to promote creativity according background, principle, objective, content, structure, measurement and evaluation. The overall quality assessment results of learning activities were appropriate at the highest level. Students' creativity​ after​ learning​ was​ higher than​ the​ criteria​ of​ 70​ percent​ with​ statistical significance at​ the​ .05​ level​ and​ students​ were​ satisfied with​ learning​ activities​ using​ creative​ theory​ at​ the​ highest​ level.